Effect of pineapple core extract on growth and saliva stimulation in Stunted Rats - Munifah Abdat; Maida Fitri; Citra Feriana Putri; Salma Salsabilla (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
Stunting refers to a condition of short stature in toddlers due to delayed growth from the prenatal period until the age of 24 months. Chronic malnutrition in stunted toddlers leads to protein deficiency; therefore, active substances are needed for maximum protein absorption. Pineapple core (Ananas comosus) contains bromelainenzymes and citric acid, whichcan enhance protein absorption in conditions of chronic malnutrition and increase saliva flow rate.This study aims to investigate the effect of pineapple core extract on growth parameters and saliva flow rate in stunted Wistar rats. This study involved 16 male Wistar rats, which were divided into four groups: a negative control group (no treatment), a treatment group (75% pineapple core extract), a positive control group 1 (FeSo4 supplements), and positive control group 2 (pilocarpine hydrochloride). Growth parameters and saliva flow rate were measured before and after pineapple core extract treatment. The research results were analyzed using one-way ANOVA followed by Tukeys test, which showed a significant difference between the treatment group and the other groups in body weight (p = 0.037), body length (p = 0.028), tail length (p = 0.003), and saliva flow rate (p = 0.000). Administration of 75% pineapple core extract resulted in increased growth parameters (body weight, body length, and tail length) and saliva flow rate in stunted rats.